Muslim Crusaders: Guzmán el Bueno and the Limits of Secular History. Issue 3 (2nd September 2018) - Fancy, Hussein
ABSTRACT: Around 1280, a Christian mercenary captain led Muslim soldiers bearing crosses on their chests, in the fashion of crusaders, into battle against other Muslims. At least, this is what Pedro Barrantes Maldonado reported in his Ilustraciones de la casa de Niebla about the well-known nobleman, Don Alfonso Pérez de Guzmán, later called Guzmán el Bueno (Guzmán the Good) and the Muslim soldiers under his command in Morocco. Rather than simply dismissing this episode as fiction, as it has been in the past, this essay interrogates that impulse to dismiss, which it identifies with an enduring secular bias in the study of religious encounters in the medieval Mediterranean. Using Latin, Arabic and Romance sources, this essay places the history of Guzmán el Bueno in a broader context, arguing that moments such as that from Barrantes Maldonado point towards a more complex picture of religious interaction than imaginable in secular terms.